(FeNiMnCrV) Nx hydrogen permeation resistance coating and preparation method thereof
The preparation of (FeNiMnCrV) Nx hydrogen-resistance coating through multi-arc magnetic filtration cathode vacuum arc technology has solved the problems of poor hydrogen-resistance coating effect and complex and high cost in the prior art, and achieved efficient and uniform hydrogen-resistance effect and Low cost production.
Patent Information
- Application Number
- CN202411573589.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing hydrogen-resistance coatings have poor results in hydrogen diffusion and permeability, and the preparation method is complex and costly. Traditional ceramic coatings are prone to failure, and new two-dimensional sheet materials are difficult to produce and disperse uniformly on a large scale.
The Nx hydrogen-resistance coating was prepared in a vacuum environment using multi-arc magnetic filtration cathode vacuum arc technology. The dense, high-quality hydrogen-resistance coating was formed by deposition of FeNiMnCrV and N2 to control nitrogen content and bias voltage. To adjust the crystal structure and membrane-based binding force.
A (FeNiMnCrV)Nx coating with high density, few defects and excellent hydrogen resistance performance was obtained, which effectively inhibited hydrogen diffusion and penetration, reduced the risk of hydrogen damage, simplified the preparation process and reduced costs.
Smart Images

Figure CN119194355A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a (FeNiMnCrV)Nx hydrogen permeation barrier coating and a preparation method thereof, belonging to the field of plating of metal materials. Background Art
[0002] Hydrogen is a new type of clean energy. However, since the radius of hydrogen atoms is smaller than that of metal atoms, hydrogen atoms are particularly prone to diffusion and penetration in metal structural materials, causing brittle fracture of the materials, which may cause serious property losses and casualties. Therefore, preventing hydrogen damage and improving the safety of hydrogen transmission and transportation have become key issues in the research of hydrogen pipelines. Coating the surface of pipeline steel to hinder hydrogen diffusion and reduce hydrogen penetration is the most effective way to reduce hydrogen damage and hydrogen embrittlement. Therefore, hydrogen barrier coatings came into being.
[0003] At present, the existing hydrogen barrier coatings mainly include traditional hydrogen barrier coatings such as oxide coatings, nitride coatings, carbide and other ceramic coatings, and new hydrogen barrier coatings such as two-dimensional sheet materials dominated by graphene. Traditional ceramic coatings usually face the problem of large difference in thermal expansion coefficient with the substrate, easy to crack, and easy failure of the coating. New two-dimensional sheet materials usually face the problem of being unable to be mass-produced and easily dispersed unevenly in the coating.
[0004] High entropy nitrides, like other high entropy materials, also have four special effects. The serious lattice distortion can effectively prevent the penetration and diffusion of hydrogen atoms. Due to the cocktail effect, the interaction between different elements and H atoms can produce a local capture effect, which hinders the penetration of H atoms. In addition, due to the huge potential energy difference between different positions, the energy rugged landscape is further restricted. The existing methods for preparing high entropy nitride coatings are mostly magnetron sputtering, which has complex technical processes, expensive equipment, and high costs. Secondly, the prepared single nitride coatings such as TiN and CrN still have problems such as insufficient structure, more particles and defects on the coating surface, which leads to low hydrogen blocking efficiency. Multi-arc magnetic filtered cathode vacuum arc ion plating technology (Co-FCVA) technology is an energetic particle beam deposition technology developed on the basis of vacuum arc deposition technology. It is widely used because of its 100% ionization rate and fast deposition rate. In addition, Co-FCVA overcomes the problem of macroscopic particle contamination in traditional cathode vacuum arc deposition technology by filtering out non-ionized atoms to produce high-quality plasma and high-quality films. In addition, by setting up multiple targets in the chamber, the cost of preparing alloy targets can be reduced. At the same time, plasma with a certain energy has a special bombardment effect on the substrate material, which can improve the bonding force between the film and the substrate. Therefore, the film prepared by Co-FCVA deposition technology is tightly bonded to the substrate, which can effectively adjust the structure and performance of the film. Summary of the invention
[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating.
[0006] The second object of the present invention is to provide a (FeNiMnCrV)Nx hydrogen permeation barrier coating prepared by the above-mentioned preparation method. The (FeNiMnCrV)Nx hydrogen permeation barrier coating provided by the present invention has high density, few defects, and strong hydrogen barrier performance, and is suitable for surface treatment of pipeline steel, bottles, etc. in hydrogen environments.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating. The method comprises the following steps: using a multi-arc magnetic filtering cathode vacuum arc system, etching a FeNiMn alloy target, a pure chromium target and a pure vanadium target on the surface of a base material in a vacuum environment to obtain a FeNiMnCrV sputtering layer; subsequently, introducing N2, and continuously using a FeNiMn alloy target, a pure chromium target and a pure vanadium target to deposit on the surface of the base material to obtain the (FeNiMnCrV)Nx hydrogen permeation barrier coating.
[0009] The preparation method of the present invention adopts multi-arc magnetic filtration cathode vacuum arc technology, and firstly performs surface treatment on the base material before coating by sputtering to obtain a FeNiMnCrV sputtering layer, which can clean the base material on the one hand and increase the film-base bonding strength on the other hand, and then N2 is used as the reaction gas to continue to deposit the (FeNiMnCrV)Nx hydrogen permeation barrier coating by multi-arc magnetic filtration cathode vacuum arc technology. The (FeNiMnCrV)Nx hydrogen barrier coating prepared by the present invention has high film-base bonding strength, high coating density, few coating surface defects and low surface roughness, and has excellent hydrogen barrier performance.
[0010] The scheme of the present invention has no excessive restrictions on the material of the base material, such as silicon wafer, copper foil, carbon paper, steel or non-conductive polymer, etc. are all applicable.
[0011] In a preferred embodiment, the base material is made of steel, preferably 316L or 304 stainless steel. This preferred embodiment is based on the application of the hydrogen barrier coating of the present invention on the surface of pipelines and bottles in hydrogen environments, which are usually made of steel.
[0012] In a preferred embodiment, the roughness of the base material is 0.04-0.15.
[0013] Taking API X70 pipeline steel with a size of 40 × 40 × 1 mm as an example, in the actual operation process, its surface is first ground and polished to a surface roughness of 0.04~0.15, and then ultrasonically cleaned with acetone, ultrapure water and alcohol for 10 min respectively, and finally dried in a 60℃ oven for 2 h for use.
[0014] In a preferred embodiment, the FeNiMn alloy target material has the following composition, calculated by mass percentage: 15-25 wt.% iron, 15-25 wt.% nickel, and 50-70 wt.% manganese.
[0015] The inventors found that only by selecting the FeNiMn alloy target with the above-mentioned composition, and then cooperating with pure chromium target and pure vanadium target, can a coating with excellent performance be formed. However, if the composition of the target is unreasonable, the coating may not even be obtained. For example, for the FeNiMn alloy target, when the atomic ratio of Fe, Ni and Mn is 1:1:1, it may be affected by the overall magnetism of the mixed plasma in this system, or the size of the magnetic field in the magnetic filtration system, and it may not be able to stably start an arc to generate plasma.
[0016] In a preferred embodiment, the purity of the FeNiMn alloy target is ≥99.95%, the purity of the pure chromium target is ≥99.80%, and the purity of the pure vanadium target is ≥99.80%.
[0017] In a preferred embodiment, the vacuum degree of the multi-arc magnetic filtration cathode vacuum arc system is 2.0-3.0× 10 -3 In the actual operation process, the vacuum degree of the multi-arc magnetic filter cathode vacuum arc system chamber is first controlled at 2.0~3.0× 10 -3 Pa. Then set the current of the three targets corresponding to the arc head.
[0018] The preferred scheme is to etch the FeNiMn alloy target, pure chromium target and pure vanadium target on the surface of the substrate material by setting the current of the arc head corresponding to the FeNiMn alloy target to 45~70 A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 70~90A, and then use bias voltages of -800V, -600V, -400V and -200V for etching for 30~45s respectively. In the present invention, a relatively high bias voltage is first used to etch the substrate material to clean the surface of the substrate material, and then a bias voltage with slightly lower energy is gradually used to plate a layer of metal film to form a so-called pinning layer to increase the film-base bonding strength. The magnitude and time of the bias voltage are adjusted to obtain a FeNiMnCrV sputtering layer of a specific thickness. If the bias voltage is too large and the time is too long, defects such as pits may appear on the material surface. If the thickness is too thick, it may affect the subsequent film growth mode. If it is too thin, it may affect the film-base bonding strength.
[0019] In a preferred embodiment, the thickness of the FeNiMnCrV sputtered layer is 20-30 nm.
[0020] In a preferred solution, the flow rate of N2 is 12~48sccm, preferably 24~48sccm, and more preferably 36~48sccm. The inventors found that the flow rate of N2 has a great influence on the performance of the formed (FeNiMnCrV)Nx. When N is not contained, the resulting coating presents a coarse columnar crystal structure. As the N content increases, the grain size first decreases with the increase of the N content, and the crystal form first changes from a BCC structure to an amorphous structure, and then to an FCC phase structure with (111) and (200) as preferred orientations, and then to an FCC phase structure with (200) as preferred orientation until the nitrogen content reaches saturation. However, when the nitrogen content reaches saturation, the grain size begins to increase. Therefore, the flow rate of N2 is controlled within the scope of the present invention to obtain a coating with fine, dense grains and preferred orientation. If the flow rate of N2 is too low, the internal disorder is high, forming an amorphous structure without complex H atom diffusion paths at grain boundaries. If the N content in the coating is high, the grain size increases and the density of the coating changes. Among them, S-36sccm with fine grain size and preferred orientation (200) has the best electrochemical resistance to hydrogen permeation. app and J are 49 and 84 times lower than those of uncoated X70, respectively.
[0021] The preferred solution is to use FeNiMn alloy target, pure chromium target, and pure vanadium target to deposit on the surface of the substrate material: set the current of the arc head corresponding to the FeNiMn alloy target to 45~70 A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V to deposit for 40~80min. During the deposition process of the (FeNiMnCrV)Nx coating, the bias voltage needs to be controlled. If it is too small at 0V, the film-base bonding force is not very good, and when it is higher than -150V, the energy is too high and the structure of the film will be destroyed.
[0022] In the actual operation process, nitrogen is pre-flowed for about 30 seconds, and the arc head power is turned on after the vacuum degree in the chamber is stable. The arc power is turned off after the deposition is completed.
[0023] In a preferred embodiment, the thickness of the (FeNiMnCrV)Nx hydrogen permeation barrier coating is ≥1 μm, preferably 1-1.6 μm.
[0024] The present invention also provides a (FeNiMnCrV)Nx hydrogen permeation barrier coating prepared by the above preparation method.
[0025] Compared with the existing technology, the beneficial effects of the present invention are embodied in:
[0026] The present invention adopts multi-arc magnetic filtering cathode vacuum arc technology, firstly performs surface treatment on the base material before coating by sputtering to obtain a FeNiMnCrV sputtering layer, which can clean the base material on the one hand and increase the film-base bonding strength on the other hand, and then uses N2 as the reaction gas to continue to deposit the (FeNiMnCrV)Nx hydrogen permeation barrier coating by multi-arc magnetic filtering cathode vacuum arc technology, and the crystal structure, preferential orientation and grain size of the coating can be effectively regulated by controlling the nitrogen content, so as to obtain the (FeNiMnCrV)Nx hydrogen barrier coating with high film-base bonding strength, high coating density, few coating surface defects and low surface roughness.
[0027] At the same time, due to the sufficiently significant atomic size differences in (FeNiMnCrV)Nx, severe lattice distortion can hinder the diffusion of H atoms. There is a significant potential energy difference at different positions, which produces a rough energy rugged landscape during hydrogen migration, greatly inhibiting hydrogen migration. In addition, the electronic interaction between hydrogen and different metal elements leads to a significant local capture effect, which limits its long-range hydrogen transport, thereby preventing most hydrogen atoms from continuing to penetrate downward and greatly reducing the hydrogen permeability.
[0028] Under the above synergistic effect, the (FeNiMnCrV)Nx hydrogen barrier coating provided by the present invention has excellent hydrogen barrier effect.
[0029] The preparation method of the present invention is simple to operate, has low preparation cost, and has a more uniform coating, and can effectively improve the hydrogen barrier performance and service performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a design diagram of the (FeNiMnCrV)Nx structure involved in the present invention.
[0031] Figure 2 The surface morphology and cross-sectional morphology of the (FeNiMnCrV)Nx coating involved in the present invention are shown.
[0032] Figure 3 This is a current-time hydrogen permeation curve of the prepared (FeNiMnCrV)Nx coating, where the right side is a local enlarged view of the left side. DETAILED DESCRIPTION
[0033] The preparation of the (FeNiMnCrV)Nx hydrogen barrier coating structure prepared by the present invention is further described below by means of specific examples:
[0034] Example 1
[0035] In this example, the (FeNiMnCrV)Nx hydrogen barrier coating on the surface of the pipeline steel is applied to the surface of API X70 pipeline steel. The preparation steps are as follows:
[0036] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0037] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0038] 3. First, control the vacuum degree in the chamber to 2.2× 10 -3 Pa. Then the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60, 80 and 75 A respectively. The X70 substrate was etched at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s respectively. The substrate was not externally heated. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0039] 4. Set the N2 gas flow rate to 12 sccm, pre-flow nitrogen for about 30 s, and wait until the gas pressure in the chamber is stable. Then, turn on the power supplies of the three arc heads of FeNiMn, Cr and V, and set the currents to 60, 80 and 75 A respectively. Deposit on the surface of X70 pipeline steel at a bias voltage of -100 V for 60 min to obtain a dense (FeNiMnCrV)Nx layer. After the deposition is completed, turn off the arc power supply. The thickness of the hydrogen barrier coating is about 1.251 μm, marked as S-12 sccm.
[0040] Example 2
[0041] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0042] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0043] 3. First, control the vacuum degree in the chamber to 3.0× 10 -3 Pa. Then the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60, 80 and 75 A respectively. The X70 substrate was etched at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s respectively. The substrate was not externally heated. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0044] 4. Set the N2 gas flow rate to 24 sccm, pre-flow nitrogen for about 30 s, and wait until the gas pressure in the chamber is stable. Then, turn on the power supplies of the three arc heads of FeNiMn, Cr and V, and set the currents to 60, 80 and 75 A respectively. Deposit on the surface of X70 pipeline steel at a bias voltage of -100 V for 60 min to obtain a dense (FeNiMnCrV)Nx layer. After the deposition is completed, turn off the arc power supply. The thickness of the multilayer hydrogen barrier coating is about 1.500 μm, marked as S-24 sccm.
[0045] Example 3
[0046] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0047] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0048] 3. First, control the vacuum degree in the chamber to 2.5× 10 -3Pa. Then the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60, 80 and 75 A respectively. The X70 substrate was etched at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s respectively. The substrate was not externally heated. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0049] 4. Set the N2 gas flow rate to 36 sccm, pre-flow nitrogen for about 30 s, and wait until the gas pressure in the chamber is stable. Then, turn on the power supplies of the three arc heads of FeNiMn, Cr and V, and set the currents to 60, 80 and 75 A respectively. Deposit on the surface of X70 pipeline steel at a bias voltage of -100 V for 60 min to obtain a dense (FeNiMnCrV)Nx layer. After the deposition is completed, turn off the arc power supply. The thickness of the multilayer hydrogen barrier coating is about 1.593 μm, marked as S-36 sccm.
[0050] Example 4
[0051] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0052] 2. Select multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) equipment, use FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, purity 99.95%) and two pure metals (containing chromium and vanadium, purity 99.80%) as targets, the thickness and diameter of all targets are 20 and 100 mm respectively, and select N2 with a purity of 99.99% as the reaction gas.
[0053] 3. First, control the vacuum degree in the chamber to 2.4× 10 -3 Pa. Then the currents of the three arc heads of FeNiMn, Cr and V targets were set to 60, 80 and 75 A respectively. The X70 substrate was etched at bias voltages of -800, -600, -400 and -200 V for 30, 30, 45 and 45 s respectively. The substrate was not externally heated. After the sputtering was completed, the arc power was turned off to obtain a FeNiMnCrV sputtered layer with a thickness of 25 nm.
[0054] 4. Set the N2 gas flow rate to 48 sccm, pre-flow nitrogen for about 30 s, and wait until the gas pressure in the chamber is stable. Then, turn on the power supplies of the three arc heads of FeNiMn, Cr and V, and set the currents to 60, 80 and 75 A respectively. Deposit on the surface of X70 pipeline steel at a bias voltage of -100 V for 60 min to obtain a dense (FeNiMnCrV)Nx layer. After the deposition is completed, turn off the arc power supply. The thickness of the multilayer hydrogen barrier coating is about 1.503 μm, marked as S-48 sccm.
[0055] Comparative Example 1
[0056] 1. The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h.
[0057] 2. A multi-arc magnetic filtered cathode vacuum arc (Co-FVCA) device was selected, with FeNiMn alloy (containing 25 wt.% iron, 25 wt.% nickel, 50 wt.% manganese, and a purity of 99.95%) and two pure metals (containing chromium and vanadium, with a purity of 99.80%) as targets. The thickness and diameter of all targets were 20 and 100 mm, respectively.
[0058] 3. First, control the vacuum degree in the chamber to 2.8× 10 -3 Pa. The currents of the three arc heads of FeNiMn, Cr and V targets were set to 60, 80 and 75A respectively. On the X70 substrate, the bias voltages of -800, -600, -400 and -200 V were used for etching for 30, 30, 45 and 45 s respectively. The substrate was not externally heated, and a FeNiMnCrV sputtered layer with a thickness of 25 nm was obtained. The bias voltage was then adjusted to -100 V, and the deposition was carried out for 60 min to obtain a FeNiMnCrV layer with a thick columnar crystal structure without N. After the deposition was completed, the arc power was turned off. The thickness of the hydrogen barrier coating was about 1.054 μm, marked as S-0sccm.
[0059] Comparative Example 2
[0060] The API X70 pipe steel with a size of 40 × 40 × 1 mm was surface-polished to a surface roughness of 0.04~0.15, and then the substrate was ultrasonically cleaned for 10 min using acetone, ultrapure water and alcohol, and finally dried in a 60°C oven for 2 h for use without subsequent coating treatment and marked as Bare-X70.
[0061] Performance Testing
[0062] Figure 2 The microscopic images of the coatings obtained in Comparative Example 1 and Examples 2-4 are respectively. From the cross-sectional morphology of the coatings, it can be observed that the coatings (without N) present a coarse columnar crystal structure. The introduction of N makes the coatings become an equiaxed crystal structure. The grain size first decreases with the increase of N content, and then when the N content in the coating reaches saturation, the grain size increases again. The crystal structure and preferred orientation also change with the change of N content. It can be seen that when there is no N, it is a BCC structure. When the N2 flow rate is 24 sccm, it presents a preferred orientation with (111) and (200). As the N2 flow rate increases, when the N2 flow rate is 36sccm, the FCC phase structure with (200) as the preferred orientation appears, and then until the N2 flow rate is 48sccm, it still presents an FCC phase structure with (200) as the preferred orientation. However, since the nitrogen content reaches saturation when the N2 flow rate is 48sccm, it can be seen that the grain size is larger than that of the coating with an N2 flow rate of 36sccm, that is, from the overall point of view, the grain size and surface roughness show a trend of first decreasing and then increasing as the N content reaches saturation.
[0063] Figure 3 1 is a graph showing the current-time hydrogen permeation curves of the embodiment and the comparative example (FeNiMnCrV)Nx coating, wherein the right side is a partial enlarged view of the left side.
[0064]
[0065] from Figure 3 As can be seen from Table 1, when the N2 flow rate is 36 sccm, the coating performance is optimal. This is because the FCC phase structure with (200) as the preferred orientation has better hydrogen barrier performance than other crystal structures, and when the N2 flow rate is 36 sccm, the grains are smaller and denser than when the N2 flow rate is 48 sccm.
[0066] Finally, it should be noted that the above examples are only specific implementation examples of the present invention. Obviously, the present invention is not limited to the above examples, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating, characterized in that: Through a multi-arc magnetic filtered cathode vacuum arc system, in a vacuum environment, FeNiMn alloy target, pure chromium target and pure vanadium target are etched on the surface of the base material to obtain a FeNiMnCrV sputtering layer. Subsequently, N2 is introduced and FeNiMn alloy target, pure chromium target and pure vanadium target are continuously deposited on the surface of the base material to obtain a (FeNiMnCrV)Nx hydrogen penetration barrier coating.
2. The method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1, characterized in that: The base material is made of steel. The roughness of the base material is 0.04-0.
15.
3. A method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1 or 2, characterized in that: The FeNiMn alloy target material has the following composition by mass percentage: 15-25 wt.% of iron, 15-25 wt.% of nickel, and 50-70 wt.% of manganese; The purity of the FeNiMn alloy target material is ≥99.95%, the purity of the pure chromium target material is ≥99.80%, and the purity of the pure vanadium target material is ≥99.80%.
4. A method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1 or 2, characterized in that: The vacuum degree of the multi-arc magnetic filtration cathode vacuum arc system is 2.0~3.0×10 -3 Pa.
5. The method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1, characterized in that: The process of etching the FeNiMn alloy target, pure chromium target and pure vanadium target on the surface of the substrate material is as follows: set the current of the arc head corresponding to the FeNiMn alloy target to 45~70A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 70~90A, and then use bias voltages of -800V, -600V, -400V and -200V for etching for 30~45s respectively.
6. A method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1 or 5, characterized in that: The thickness of the FeNiMnCrV sputtered layer is 20-30 nm.
7. The method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1, characterized in that: The flow rate of N2 is 12~48 sccm.
8. A method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1 or 7, characterized in that: The process of depositing FeNiMn alloy target, pure chromium target and pure vanadium target on the surface of the substrate material is as follows: set the current of the arc head corresponding to the FeNiMn alloy target to 45~70A, the current of the arc head corresponding to the pure chromium target to 80~110 A, and the current of the arc head corresponding to the pure vanadium target to 75~90A, and then use a bias voltage of 0V~-150V for deposition for 40~80min.
9. The method for preparing a (FeNiMnCrV)Nx hydrogen permeation barrier coating according to claim 1 or 2, characterized in that: The thickness of the (FeNiMnCrV)Nx hydrogen permeation barrier coating is ≥1 μm.
10. The (FeNiMnCrV)Nx hydrogen permeation barrier coating prepared by the preparation method according to any one of claims 1 to 9.
